Pengembangan Media Pembelajaran IPA Berbasis Android â€œWismayaâ€ dengan Pendekatan Inkuiri dalam Meningkatan Kemampuan Berpikir Kritis Siswa Kelas IV Materi Gaya - Sarida Nur Asani; Arief Yulianto; Nuni Widiarti (Postgraduate, University of Mataram, 2023)
This study aims to develop an android-based game learning media by applying the steps of the ADDIE model RnD research method. The data collection technique was in the form of a validated questionnaire for media experts, linguists, materials, teachers, and student responses. The results of media, material, and language validation were 0.917; 0.898, and 0.791 with very feasible criteria for media and material validation, while for language validation it shows feasible criteria. The classical mastery of student learning outcomes reached 94% and the N percent gain of 59.34 indicated that the criteria were quite effective. Student responses were seen from the usefulness, convenience, and satisfaction indicators each of 0.82; 0.9; and 0.92 indicating very good response criteria. The teacher's response questionnaire, seen from the indicators of presentation and use of language, was 0.9 and 0.875 respectively, indicating very good response criteria, while in the indicators of instructions for use, the suitability of the material and suitability for student needs were each 0.75; 0.8; and 0.79 indicates good response criteria. The results of the application of android-based science learning media with an inquiry approach can improve the critical thinking skills of class IV students on style material.